Indexing integration: hierarchies of belonging in secular Paris - Yount-André, C (Anthropological Society of Oxford, 2017)
In the wake of terrorist attacks in Paris in 2015, stereotypes of Muslim migrants who pose a threat to the French nation loom large. This article considers how communicative practices associated with belonging in France shift with rising tensions surrounding Islam and immigration. By analyzing the language used in state discourses on the one hand, and in conversations in Senegalese households on the other, this article examines ‘integration' in France, both as a legal category and as a powerful metapragmatic framework that mediates indexicality in everyday interactions. This article shows how immigrants take part in the continual redefinition of what is required to ‘sound' integrated in attempts to illustrate their belonging in France. It contends that French republican ideologies create an axis of contrast between the ‘integrated' foreign-born and potentially problematic ‘immigrants,' revealing how immigrants appropriate state discourses in their efforts to demonstrate their own integration. In so doing, immigrants themselves produce nested hierarchies of belonging among France's immigrant minority populations, in which Senegalese Catholics perform integration through critiques of Muslims, while Senegalese Muslims denounce Islamic associations and others who are more pious in public than they.